SOSIALISASI PENGGUNAAN METODE PEMBELAJARAN BLENDED LEARNING DI MASA PANDEMI BAGI GURU DI MA ALKAHFI BOGOR - Maya Nurfitriyanti; Fatwa Patimah Nursa’adah; Aulia Masruroh (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2021)
The Covid-19 pandemic has forced us to make habits that we never imagined before. This also triggers changes in the learning system from primary education to higher education. One of the changes in the education system is the distance learning system (PJJ). In this condition, teachers must quickly adjust the new policies issued by the government, namely by learning activities and teaching students from home to prevent the spread of COVID-19. One of the efforts to do so that learning runs effectively is the blended learning method. Blended learning combines computer and internet technology offered by online learning and face-to-face learning participation to provide the most effective and efficient experience. Using the correct learning methods, overcoming learning obstacles due to COVID-19 can be overcome. With the blended learning method, students learn independently, and teachers can continue to explain the subject matter using learning media such as the internet.